Relativistic configuration-interaction calculation of energy levels of core-excited states in lithiumlike ions: argon through krypton - Yerokhin, Vladimir; Surzhykov, Andrey (Physical review. A, Atomic, molecular, and optical physics, 2012)
Large-scale relativistic configuration-interaction calculation of energy levels of core-excited states of lithium-like ions is presented. Quantum electrodynamic, nuclear recoil, and frequency-dependent Breit corrections are included in the calculation. The approach is consistently applied for calculating all n=2 core-excited states for all lithium-like ions starting from argon (Z=18) and ending with krypton (Z=36). The results obtained are supplemented with systematical estimations of calculation errors and omitted effects.